Stability analysis of closed loop TRMS with observer based reliable H infinity controller using Kharitonov’s stability theorem - S. Rao, Vidya; I. George, V; Kamath, Surekha; Shreesha, C (International Journal of Engineering and Technology, 2018)
The laboratory Twin Rotor Multiple Input Multiple Output System (TRMS) serving as a model of a helicopter has un modeled errors in its model, due to linearization, measurement errors, equipment wear, sensors or/and actuator failures. This mismatch is termed as uncertainties in the model. Due to sensor and actuator failure there would exist a large range of uncertainties. In this paper, the range of robust stability bound for closed loop TRMS along with observer based reliable H infinity controller using Kharitonov’s stability theorem is found. The variation in parameters of TRMS from its nominal values are shown. The Kharitonov’s stability analysis on TRMS proves that within the mentioned uncertainty limit the TRMS along with observer based reliable H infinity controller gives the closed loop stable response.